Análise comparativa técnico-econômica entre os pavimentos de concreto asfáltico e blocos intertravados de concreto - Oliveira, Cinara Souza de (Universidade do Vale do Rio dos Sinos, 2018)
This dissertation aims to compare economically the asphalt concrete and interlocking concrete blocks in the urban paving of Severo Dullius Avenue, considering the costs of the solutions proposed by the methods. The avenue under study is one of the main radial roads that makes up the ring road that accesses the Salgado Filho International Airport, and it is considered imperative to the urban mobility plan of the city of Porto Alegre / RS, located in and urban swamp area, with subsoil consisting of low support power soils and heavy commercial traffic. The sizing was carried out for a 2.3 km stretch, and it was based on geotechnical studies in order to physically and mechanically characterize the subsoil soil, considering the counting and classification of the traffic acting on the road. Next, the structural behavior of these urban pavements in the mentioned situation was analyzed and the suitable and recommended construction methods were presented. The method of sizing of flexible pavement – DNER current DNIT was applied to the asphaltic pavement, and the ABCP (1998) method was used for the interlocked block of concrete. In order to allow the technical and financial comparison between the floors, their structural characteristics and the respective project periods were considered. The costs of implementation and conservation were taken into account. With the budgets available, a comparison of services was carried out in order to identify their economic viability, thus proposing the adequate pavement for the selected route. It was concluded for this study that, as a final solution, the use of the interlocked concrete block compared with the concrete, showed a saving of 16,93% in the final cost of the implantation, thus economically more advantageous in relation to the asphalt concrete. In view of this, it was also concluded that an economic analysis of a road pavement should always address all relevant costs and benefits, considering all phases of its implementation.
Keywords: Blocos intertravados; Concreto asfáltico; Método; Pavimento; Tráfego; Interlocking blocks; Asphalt concrete; Method; Pavement; Traffic; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo